PLANNING OF RESOURCE PROVISION OF EXIT FROM THE CRISIS OF THE ENTERPRISES OF THE HOTEL AND RESTAURANT - VLASENKO, IVAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the impact of the COVID-19 pandemic on the functioning of small and medium-sized businesses in the hotel and restaurant industry. The hotel and restaurant business in Ukraine suffers the most from the restrictions imposed due to the spread of the virus. The established restrictions have both direct and indirect impact on the functioning of small and medium-sized businesses in the hotel and restaurant industry. It is shown that due to the introduced restrictions, the share of the hotel and restaurant business sector in the gross domestic product of Ukraine has significantly decreased, employment in this sector has decreased. During the quarantine restrictions, the hotel and restaurant business faced a number of problems: low access to finance; loss of access to markets; complex regulation and tax pressure. To overcome the problems facing the small and medium business sector in the hotel and restaurant sector, it is necessary to maintain business activity and jobs; increase institutional capacity to operate in markets. Quarantine measures have created a significant negative impact on the work of the small and medium business sector, which may be exacerbated in the absence of government intervention. Quarantine measures have created a significant negative impact on the work of SMEs, which may be exacerbated in the absence of government intervention. A significant problem for the hotel and restaurant business is the rapid restructuring in accordance with the new social standards in a pandemic, which will allow to work and make a profit, as well as to protect their customers from the risk of infection and minimize the threat of COVID-19. The article outlines a number of major problems faced by the hotel and restaurant business during quarantine restrictions and tasks that need to be addressed to overcome them.